Improvement of the Regulatory Framework of Regulation of Transnational Business in Azerbaijan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Though formation of the transnational business is based on common principles, this process appears in a specific form in various countries. Transnational business is different depending on the structure of the economy, the level of socio-economic development, organizational and management structure, national-ethnic characteristics, and the level of development of the state in various countries. At the same time, creating and justifying the fact that big, fast-growing and concentrated national companies are ranked in the rankings as TNB (transnational business) is one of the issues within the interest of state and economic science. Upon the Contract of the Century signed in September 1994, Azerbaijan has subsequently signed the production sharing agreements (PSAs) on “Garabakh”, “Dan ulduzu” and “Ashrafi” fields. The biggest TNBs, such as BP, Amoko, Penzoil and Unocal, have their share in oil fields from Azerbaijan. Up to 70% of all investments in the Azerbaijani economy are invested in the oil industry, about 80% of which is imposed by the foreign TNBs. This figure indicates that the TNB has a great role in the economy of Azerbaijan.TNB has both positive and negative impacts on the economy of Azerbaijan. As Azerbaijan’s transnational business develops, various problems also arise. For instance, the problems between the TNB and the Azerbaijan Trade Unions Department, the problems between Britis Petrolium and the Azerbaijan Government, etc. The problems they face with the host countries have begun to show itself in Azerbaijan too. Transnational business regulation is a very urgent issue over the world. The scientists have increasingly investigated the legal aspects of the TNB regulation. This article is dedicated to the actions that are being taken and important to be taken to regulate transnational business at the state level in the Republic of Azerbaijan, and the regulation methodology is proposed.